Safety and Efficacy of Misoprostol versus Oxytocin for the Prevention of Postpartum Hemorrhage - Minoo Rajaei; Samieh Karimi; Zohreh Shahboodaghi; Hamidreza Mahboobi; Tahereh Khorgoei; Farzam Rajaei (Hindawi Limited, 2014)
Postpartum hemorrhage (PPH) is the commonest cause of maternal death worldwide. Studies suggest that the use of misoprostol may be beneficial in clinical settings where oxytocin is unavailable. The aim of this study was to compare the safety and efficacy of oxytocin and misoprostol when used in the prevention of PPH. In a double-blind randomized controlled trial, 400 pregnant women who had a vaginal delivery were assigned into two groups: to receive either 20 IU of oxytocin in 1000 mL Ringer's solution and two placebo tablets or 400 mcg oral misoprostol (as two tablets) and 2 mL normal saline in 1000 mL Ringer's solution. The quantity of blood loss was higher in the oxytocin group in comparison to the misoprostol group. There was no significant difference in the decrease in hematocrit and hemoglobin between the two groups. Although there was no significant difference in the need for transfusions between the two groups, the patients in the oxytocin group had greater need for additional oxytocin. Results from this study indicate that it may be considered as an alternative for oxytocin in low resource clinical settings. This study is registered with ClinicalTrials.gov NCT01863706.